Kelayakan Perangkat Pembelajaran Model Teams Games Tournament Berbantuan Question Card pada Materi Sistem Reproduksi di SMA - Jeki, Jeki; Ningsih, Kurnia; Tenriawaru, Andi Besse (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research was conducted to improve the learning process that has been carried out by teachers in delivering learning material which still uses conventional learning models which results in a bored learning atmosphere and students are not motivated in learning which ultimately causes low student learning outcomes, especially in biology lessons. The aim of this research is to determine the feasibility of a team games tournament model learning tool assisted by question card media on reproductive system material in high school. This type of research is Research and Development (R&D) or research and development with 5 stages, namely stages; potential and problems, gathering information, product design, design validation, and design revision. The products produced in this research are learning tools in the form of RPP, LKPD, and Powerpoint media as well as Question card media. The research results show that the validated learning tools are declared valid, this is because the average statement has a value above the validity standard set by researchers in accordance with Aiken's V calculation rules, namely that each item V â‰¥ 0.87. For RPP the average statement value is 0.93, for LKPD the average statement value is 0.92, for PPT the average statement value is 0.93. And for media Question cards, the average statement value is 0.95. From the results obtained, it can be stated that the learning tools developed are feasible and can be used in the learning process.